Should data monitoring committees assess efficacy when considering safety in trails in acute stroke? - Bath, Philip M.W.; Gray, Laura J.; Wahlgren, Nils-Gunnar (Blackwell Publishing, 2007)
The primary role of a trials Data Monitoring Committee (DMC) is to ensure the safety of enrolled patients. In stroke trials, safety is monitored typically by comparing death and stroke specific events between treatment groups. DMCs may also have the remit for monitoring efficacy depending on the aims of the trial. We hypothesised that functional outcome at end of follow-up, a measure of efficacy, is also a powerful measure of safety and tested this in a systematic review